Androgen deprivation therapy for the treatment of prostate cancer: a focus on pharmacokinetics. (2nd December 2017) - Polotti, Charles F.; Kim, Christopher J.; Chuchvara, Nadiya; Polotti, Alyssa B.; Singer, Eric A.; Elsamra, Sammy
ABSTRACT: Introduction : Medical therapy has undergone many changes as our understanding of prostate cancer cell biology has improved. Androgen deprivation therapy (ADT) remains the mainstay of therapy for metastatic disease. Metastatic castrate-resistant prostate cancer (CRPC) is an important concern since we are unable to stop progression with currently available agents. Areas covered : Pharmacologic ADT is the most commonly used treatment for metastatic prostate cancer. Multiple agents are available for both first-line and second-line use: antiandrogens, estrogens, luteinizing hormone-releasing hormone agonists/antagonists, and CYP17 inhibitors. With adoption of these drugs, it is important to consider their pharmacokinetic and pharmacodynamic properties. Many undergo metabolism through cytochrome P450. Levels may be altered with co-administration of drugs acting as enzyme inhibitors or inducers. Understanding mechanism of action, metabolism, and excretion of these drugs allows clinicians to provide the best therapeutic care while minimizing adverse events. Expert opinion : Many men with metastatic prostate cancer will progress to castration resistance. An understanding of resistance mechanisms at the cellular level has revealed new drug targets with hopes of halting or reversing progression of metastatic disease. Second-line agents, traditionally reserved for CRPC, are being studied in metastatic castrate-sensitive prostate cancer, and may offer practice-changing evidence supporting their use.